Blended Learning Pedagogy and the Development of Digital Competences among Teacher Trainees in a Predominantly Face to face Teacher Education Program - Buluma, Alfred; Walimbwa, Michael (SN Social Sciences, 2021)
This paper examines the influence of blended pedagogy in facilitating the development of digital competences among teacher trainees in a leading University in Uganda. This is an action research that took place between August and November, 2019, in which data were collected from third-year teacher trainees at School of Education in a pre- and post-intervention survey environment. At the beginning of August 2019, a self-administered questionnaire (SAQ) seeking the opinions about the teacher trainees’ digital competences was administered. In the course of the semester, the researchers introduced a blended pedagogy approach through offering online tutorials to the teacher trainees using a MOODLE learning management system referred to as Makerere University Electronic Learning Environment (MUELE) in the course unit known as Evaluation of Instruction. Prior to the beginning of semester one examinations in November 2019, the same SAQ was administered to teacher trainees to examine the influence of blending online tutorials in nurturing their digital competences. Findings indicate improved competences in teacher trainees’ digital competences in line with navigation in the internet environment, operating mobile internet, operating internet-based search engines, and formal internet skills. Other competences that teacher trainees demonstrated improvement include digital information and communication competences. The study, however, indicated minimal improvement in teacher trainees’ digital competences in content creation. Consequently, it is recommended that teacher educators should deliberately adopt the use of blended pedagogy to enable teacher trainees develop the various digital competences expected from the twenty-first-century teacher.
Keywords: Blended pedagogy · Digital competences · Teacher education · Teacher trainees